Theoretical Analysis of Velocity and Position Loop Behaviour of Nonlinear Cascade Feedforward Controller for Positioning of XY Table Ballscrew Drive System - Abdullah, Lokman; Jamaludin, Zamberi; Salleh, Mohd Rizal; Abu Bakar, Baharudin; Jamaludin, Jailani; Tsung Heng, Chiew; RAFAN, NUR AIDAWATY (Trans Tech Publications, 2014)
The trend in machine tools and positioning systems nowadays are demanding for accuracy, precision and robustness attributes. In addition to those characteristics, a low-cost and adaptive control systems towards various disturbance forces also add a significant advantage to control engineers who can fulfill those needs. The objective of this paper is to introduce a newly improved control strategy named as Nonlinear Cascade Feedforward. It is basically, a cascade control structure with the additional of two add on modules called Nonlinear function plus independent feedforward function. Secondly, the aim of this article is to focus on the fundamental aspect on how to analyze the open loop and closed loop behavior for both velocity and position loop in the control structure by extracting the mathematical formulation of the controller. The outcome from this paper which is in the form of mathematical formula is beneficial and exceptionally significant during the validation and verification stage. The theoretical analysis involved are analysis on gain and phase margin, bandwidth frequency, sensitivity function, position error and finally analysis on dynamic stiffness of the system which is in this case the XY Table Ballscrew drive system. The strength of this controller is the self-adjusting mechanism towards variable disturbance cutting forces. Based on mathematical formulation, it is observed that the designed nonlinear cascade feedforward offer more flexibility and robustness in terms of the ability to compensate the tracking errors at variable disturbances.